2010
DOI: 10.1016/j.curtheres.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naloxone and flumazenil on antinociceptive action of acetaminophen in rats

Abstract: Flumazenil antagonized the analgesic effect exerted by acetaminophen, while naloxone had no significant effect on acetaminophen's antinociceptive action in this pain model in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Interestingly, the combination of vitexin and acetaminophen showed clear infra-additive or antagonistic interaction. Recent evidence indicated that the antinociceptive action of acetaminophen is antagonized by flumazenil, a benzodiazepine sensitive GABA A receptor antagonist, which suggests GABA A receptors play an important role in acetaminophen-induced analgesia 45 . Our study also reveals the involvement of GABA A receptors in vitexin-induced analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the combination of vitexin and acetaminophen showed clear infra-additive or antagonistic interaction. Recent evidence indicated that the antinociceptive action of acetaminophen is antagonized by flumazenil, a benzodiazepine sensitive GABA A receptor antagonist, which suggests GABA A receptors play an important role in acetaminophen-induced analgesia 45 . Our study also reveals the involvement of GABA A receptors in vitexin-induced analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, they found out that the enhancement in antinociceptive action made by 100 mg kg -1 acetaminophen was blocked by naloxone. In their study, Madenoglu et al (19) showed that opioid receptors were blocked with naloxone and then with acetaminophen which was administered at a dose of 300 mg kg -1 . Sawadogo et al (20) showed in a mouse study that 100 mg kg -1 administration of paracetamol had an analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Madenoglu et al (14) reported that fl umazenil antagonized the antinociceptive effect of acetaminophen in rats. However, this study proposed that fl umazenil caused an analgesic effect by using GABA receptors because the mechanism of action of paracetamol has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Flumazenil, as a derivate of 1,4-imidazodiazepine, is an antagonist of benzodiazepines with partial agonist properties (13). In previous study, Flumazenil was shown to be able to antagonize the acetaminophen-related antinociceptive effect (14). These studies examined fl umazenil's potential benefi cial contribution to the reduction of APAP hepatotoxicity.…”
mentioning
confidence: 99%